The effectiveness of a training program based on psychological adaptation to reduce post-traumatic stress disorder (PTSD) among mothers of children returning to Khartoum State - Eltayeb, Mohamed Mohamed Nour ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2025)
This study aimed to build a training program and to know the effect of this program on reducing post-traumatic stress disorder among mothers of children returning to Khartoum State. It also aimed to know the significance of the differences between the average scores of the experimental group in the pre- and post-test. The researcher used the quasi-experimental approach on a sample of (30) mothers of children returning to Khartoum State after the war. They were divided into two experimental groups (15) mothers, which were applied to the training program for adaptation, and the other (15) mothers. The researcher used a training program based on psychological adaptation (prepared by the researcher), and the Davidson Post-Traumatic Stress Disorder Scale (translated by Dr. Abdul Aziz Thabet 2014), after confirming the characteristics of validity and reliability on them. The results of the study: post-traumatic stress disorder was high in the study sample before applying the program, and the training program based on psychological adaptation that was applied to the mothers of children had a positive effect and led to reducing post-traumatic stress disorder. The study made a number of recommendations, including affirming, activating, and incorporating the role of psychological and social services, social and psychological specialists.